Kajian Korosi Struktur Conveyor A pada Tambang Batubara PT XYZ di Kabupaten Bungo, Provinsi Jambi - Ahmad Syarifudin; Elfida Moralista; Indra Karna Wijaksana (UNISBA Press, 2022)
Abstract. Conveyor is a mining transportation tool to move minerals such as coal. This research found that the material of the steel-based conveyor structure experienced a decrease in quality caused by corrosion, because it is directly related to the external environment. The impact caused by corrosion on the conveyor structure is a reduction in thickness which causes the conveyor structure to be low, this results in reduced Remaining Service Life. Under these conditions, monitoring and maintenance activities are needed so that the Corrosion Rate on the Conveyor structure to be observed can be controlled. The purpose of this study is to determine the type of corrosion that occurs, the rate of corrosion, the Remaining Service Life and methods of corrosion control. This research methodology uses the method of measuring the thickness reduction of the Conveyor structure with a length of 118 meters divided into 3 segments above ground level. Measurement of the thickness of the Conveyor structure using the Ultrasonic Thickness Gauge TT 130 at 27 Test Points. The environmental conditions in Bungo Regency consist of moderate plains with an average air temperature of 240C with an average relative humidity of 86,91% and an average rainfall of 223,31 mm/year. The type of corrosion that occurs in the Conveyor structure is uniform corrosion. Control of this corrosion using the coating method. The coating used is a primer coating using Seaguard 5000, intermediate coating sherglass FF and top coating Aliphatic acrylic modified polyurethane. Abstrak. Conveyor merupakan alat transportasi kegiatan penambangan untuk memindahkan material bahan galian contohnya batubara. Penelitian ini diketahui bahwa material dari struktur conveyor berbahan dasar baja mengalami penurunan kualitas yang disebabkan oleh korosi, karena berhubungan langsung dengan lingkungan eksternalnya. Dampak yang ditimbulkan oleh korosi pada struktur conveyor yaitu terjadinya pengurangan ketebalan yang menyebabkan struktur conveyor menjadi rendah, hal ini mengakibatkan sisa umur pakai menjadi berkurang. Kondisi tersebut, diperlukannya kegiatan monitoring serta pemeliharaan agar laju korosi pada struktur conveyor yang akan diamati dapat terkendali. Metodologi penelitian ini menggunakan metode pengukuran pengurangan ketebalan struktur conveyor dengan panjang 118 meter terbagi dalam 3 segmen berada diatas permukaan tanah. Pengukuran ketebalan struktur conveyor menggunakan alat Ultrasonic Thickness Gauge TT 130 pada 27 Test Point. Kondisi lingkungan di Kabupaten Bungo terdiri dari dataran sedang dengan temperatur udara rata-rata 240C dengan kelembapan relatif rata-rata 86,91% serta rata-rata curah hujan 223,31 mm/tahun. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Pengendalian terhadap korosi ini menggunakan metode coating. Coating yang digunakan adalah Primer Coating menggunakan Seaguard 5000, Intermediate Coating Sherglass FF dan Top Coating Aliphatic Acrylic Modified Polyurethane.